Temporal variation of soil water and its influencing factors in hilly area of Chongqing, China - Shouqin, Zhong; Weihua, Zhang; Jiake, Lv; Chaofu, Wei (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: The paper studied the temporal variation of soil water content and its influencing factors in hilly area of Chongqing by the yearly data of 2006 and 2007. According to precipitation anomaly percentage, the year 2006 was a dry year and 2007 a normal year. For the dry year, the variations of soil moisture in all three layers (0-10 cm, 10-20 cm, 20-40 cm) were medium (CV was between 10% and 30%); while for the normal year, the variation in the layer of 0-10 cm was strong (CV was greater than 30%), and weak in the other two layers (CV was smaller than 10%). Hence, the seasonal variation is large for dry year and relative small for wet year in the humid area. For the probability distribution of soil moisture, no matter for the dry year or normal year, all the distribution in three layers have a single peak shape. However, the location of the peak appeared at different position in different layers and years, similar with the band of the peak. For factors affecting the temporal variation of soil moisture in 0-10 cm layer, during March to May, the meteorological factors like temperature, sunshine and precipitation were all inversely correlated with soil water content variation, among which the average temperature and accumulated temperature were highly significant, while sunshine and precipitation significant, both inversely. For soil physical properties, except the bulk density was inversely correlated, all other properties were all positively correlated. The organic material is positively correlated with soil water content, which showed that the organics are advantageous to soil water storage and movement, acting as a function of sponge. During the period of June to September, there was no significant relationship between soil water content and total storage. The meteorological factors of temperature, accumulated temperature and sunshine were all inversely correlated with soil water content in a highly significant way.Keywords: soil water, temporal variation, influencing factors, hilly areaDOI: 10.3965/j.ijabe.20140704.006Citation: Zhong S Q, Zhang W H, Lv J K, Wei C F. Temporal variation of soil water and its influencing factors in hilly area of Chongqing, China. Int J Agric & Biol Eng, 2014; 7(4): 47-59.